Digital Governance In The Implementation Of (Bandung Integrated Manpower Management Application) At The Bandung City Manpower Office - Theresa Shinta Ajie; Budiman Rusli; Herijanto Bekti (UNIVERSITAS PAKUAN, 2026)
The digital transformation of public governance has become a strategic agenda for local governments in responding to labor market complexity and the growing demand for more integrated public services. In the City of Bandung, this agenda is implemented through the Bandung Integrated Manpower Management Application (BIMMA), developed by the Manpower Office as an employment service platform. This study aims to analyze the characteristics of digital governance in the implementation of BIMMA, examine the alignment between organizational dynamics, external labor market demands, and digital governance practices, and assess the implications of this alignment for the effectiveness of municipal-level employment services. This study employs a qualitative exploratory approach through digital observation, policy document analysis, and a literature review, using Welchman’s (2015) digital governance framework as the analytical lens. The findings reveal a gap between theoretical expectations and practical implementation. Existing literature emphasizes the importance of data integration, algorithm-based analytics, and the government-as-a-platform approach in digital employment services. Empirically, however, BIMMA continues to function primarily as an information repository, characterized by fragmented data flows, limited analytical capacity, and weak inter-unit coordination. These findings indicate that the main constraints lie not in technological capacity, but in governance design, bureaucratic organizational culture, and the underutilization of data in decision-making processes. This study concludes that the effectiveness of digital employment services requires governance reform.